2015
DOI: 10.1021/acs.energyfuels.5b01683
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance Investigation of the Fractionation of Water–Ethanol Mixtures with Cellulose and Its Cross-Linked Biopolymer Forms

Abstract: Cellulose (CE) was cross-linked with epichlorohydrin (EPI) at variable compositions, and the fractionation properties were investigated in binary water−ethanol (W−E) solutions, including the pure solvent systems. The relative uptake of each solvent was measured using quantitative 1 H nuclear magnetic resonance (qNMR) spectroscopy. This study highlights the utility of qNMR as a rapid screening method for estimation of solvent selective fractionation in binary mixtures. The uptake properties of CE−EPI cross-link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(39 citation statements)
references
References 43 publications
0
39
0
Order By: Relevance
“…The HPCD content of the fiber samples was estimated using a quantitative NMR (qNMR) method that was adapted from a previous report [33]. A 1% (w/w) THF/DMSO-d 6 solution was prepared by adding a desired amount of THF to DMSO-d 6 to which ca.…”
Section: H Nmr Spectroscopy In Solutionmentioning
confidence: 99%
“…The HPCD content of the fiber samples was estimated using a quantitative NMR (qNMR) method that was adapted from a previous report [33]. A 1% (w/w) THF/DMSO-d 6 solution was prepared by adding a desired amount of THF to DMSO-d 6 to which ca.…”
Section: H Nmr Spectroscopy In Solutionmentioning
confidence: 99%
“…6 Biopolymer adsorbent technology that utilize starch and cellulose (CE) has gained increasing attention due to its relative abundance, low-cost, and low energy inputs with minimal infrastructure requirements for adsorptive-based fractionation. 7 In a previous study, 8,9 we reported the unique adsorption-based fractionation of water (W) from binary mixtures of water and ethanol (W–E) using biopolymer sorbents and their modified forms. Elsewhere, we reported on the unique adsorption of water vapor using starch biopolymer adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…9,12,13 In a recent isotherm study of starch–water vapor systems, 10 the importance of biopolymer–solvent (s–l) interactions was shown by markedly different thermodynamic properties of starch-based adsorbents. By comparison, the heterogeneous fractionation of water from W–E binary solutions using starch- and cellulose-based adsorbents was reported 8,9,1416 that extends beyond the pioneering work of Ladisch and Dyck. 17 However, there is a limited molecular-level understanding of the factors that govern hydration and solvent-selective fractionation in solid-solution (s–l) sorption processes, especially for native and modified (cross-linked) biopolymer systems.…”
Section: Introductionmentioning
confidence: 99%
“…While there are various strategies for the synthetic modification of cellulose, cross-linking is known to alter the physicochemical properties due to pillaring effects [4,5]. Previous studies have shown that the introduction of cross-links within a biopolymer network alters the textural, hydration, and mechanical properties, along with the chemical stability toward biodegradation [6][7][8][9][10]. The structure and physicochemical properties of cross-linked polymers related to adsorption (e.g., morphology, thermal stability, solvent swelling, crystallinity, and surface chemistry) differ compared with unmodified (native) polymers.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, a greater understanding of the physicochemical properties of cellulose and its cross-linked forms will advance the science and technology of such materials. We envisage that such biopolymer materials can be synthetically engineered for specialized solid phase extraction (SPE) of steroids or lipids for analytical to biotechnology applications to address chemical separations in complex media such as urine to water/alcohol mixtures [7,25].…”
Section: Introductionmentioning
confidence: 99%